2016
DOI: 10.4103/2230-8210.192895
|View full text |Cite
|
Sign up to set email alerts
|

Demographic details, clinical features, and nutritional characteristics of young adults with Type 1 diabetes mellitus - A South Indian tertiary center experience

Abstract: Context:Type 1 diabetes mellitus (T1DM) accounts for 5–10% of all diagnosed diabetes and the highest incidence is found in India.Aims:The main objectives were to study the demographic, clinical, and nutritional characteristics of young adults with T1DM and its effect glycosylated hemoglobin levels.Subjects and Methods:This cross-sectional study was conducted among young adults with T1DM (18–45 years of age) in a tertiary hospital in South India. Data were obtained from updated medical records. The dietary data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Similar findings have been reported in north Indian patients with T2DM, where knowledge, attitude, and practices with respect to diabetes management were found to be unsatisfactory 58 . There is evidence that academic knowledge does not always translate into positive action 53 Lack of supervision: Communication with school authorities about providing a nurse or other responsible staff to supervise procedures/meals and having a responsible adult at home do the same (in an unobtrusive manner) can improve compliance. Widespread availability of junk food : Unhealthy packaged foods are freely available in Indian markets 59 .…”
Section: Issues In Adherence With Mntmentioning
confidence: 71%
See 3 more Smart Citations
“…Similar findings have been reported in north Indian patients with T2DM, where knowledge, attitude, and practices with respect to diabetes management were found to be unsatisfactory 58 . There is evidence that academic knowledge does not always translate into positive action 53 Lack of supervision: Communication with school authorities about providing a nurse or other responsible staff to supervise procedures/meals and having a responsible adult at home do the same (in an unobtrusive manner) can improve compliance. Widespread availability of junk food : Unhealthy packaged foods are freely available in Indian markets 59 .…”
Section: Issues In Adherence With Mntmentioning
confidence: 71%
“…There are various other challenges in ensuring adherence to MNT that should be anticipated and addressed in problem‐solving sessions. Economic barriers: A systematic review of the possible barriers affecting good diabetes management found that besides attitude, beliefs and knowledge, finance resources is an important factor 51 . A study from south India noted that over 50% of patients attending an integrated diabetes clinic were daily wage earners who had to travel long distances to seek medical care, incurring travel costs besides loss of income 52,53 . A study from north India revealed that the mean direct cost of diabetes management per patient per year was 18.6% of annual family income.…”
Section: Issues In Adherence With Mntmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an association was found between having an increased HbA1c and having malnutrition according to BMI, which may be related to an imbalance in food consumption and, consequently, calories, due to fear of increased blood glucose, resulting in uncontrolled glycemic control, ketosis and other complications important for nutritional status ( 32 34 ). Another factor that can interfere with the nutritional status of patients with DM1 is diabulimia, a term that characterizes the omission of insulin doses in order to lose weight ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%